Tea Stem as a Sorbent for Removal of Methylene Blue from Aqueous Phase. (22nd September 2019) - Lee, Tzan-Chain; Wang, Shumao; Huang, Zonggui; Mo, Zhongxing; Wang, Gangxing; Wu, Zhuanrong; Liu, Chengshun; Han, Hua; Ko, Tzu-Hsing
Abstract : The potentiality of tea stem for the adsorption of methylene blue (MB) from aqueous phase was investigated. A series of operating factors, including the initial MB concentration, contact time, pH of solution, dose of tea stem, and ionic strength of solution, were conducted to understand the effect of adsorption of MB onto tea stem. Adsorption isotherm, kinetic models, thermodynamic investigation, and regenerability of tea stem were systematically investigated in this study. The experiment results revealed that the removal efficiency decreased with MB concentration and the equilibrium time of adsorption at different initial MB concentrations was approximately at 60 min. The appropriate dose of tea stem powder was found to be 4 g/L. The pHzpc of tea stem was evaluated and was observed to be 6.0 ± 0.2. The removal efficiency increased with pH ranging from 3.0 to 5.0 and remained constantly at the pH range of 5.0–11.0. The pH affected the adsorption because of the repellent power between H + and dye cation. The ionic strength was found to have a negligible effect on the adsorption. The Langmuir and Temkin isotherm models were found to be the best isotherm models to elucidate the adsorption mechanism between MB and tea stem powder. The maximum adsorption capacity of 103.09 mg/g derived from the Langmuir model was much close to the experimental result. From the kinetic analysis, the pseudo-second-order model was found to be the suitable model to describe the adsorption behavior. The calculated adsorption capacities at different temperatures derived from the pseudo-second-order model ranging from 68.91 to 69.8 mg/g were well close to the experimental data. The intraparticle diffusion of MB molecules into pore structures of tea stem powder is the rate-limiting step for the adsorption process in this study. Evaluation of thermodynamic parameters including changes in enthalpy, entropy, and Gibb's free energy indicated the adsorption mechanism between MB and tea stem powder was a spontaneous and exothermic process. The regeneration/adsorption experiments indicated that the tea stem powder efficiently remained more than 97% after five cycles using NaOH as a desorbing agent and thus be used for many times. On the basis of experimental results obtained, it is concluded that the tea stem has a considerable potential as a low-cost sorbent for removing MB from the aqueous phase.